Mental health nurses' attitudes, experience, and knowledge regarding routine physical healthcare: systematic, integrative review of studies involving 7,549 nurses working in mental health settings - Geoffrey L. Dickens; Robin Ion; Cheryl Waters; Evan Atlantis; Bronwyn Everett (BMC, 2019)
Abstract Background There has been a recent growth in research addressing mental health nurses' routine physical healthcare knowledge and attitudes. We aimed to systematically review the empirical evidence about i) mental health nurses' knowledge, attitudes, and experiences of physical healthcare for mental health patients, and ii) the effectiveness of any interventions to improve these aspects of their work. Methods Systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Multiple electronic databases were searched using comprehensive terms. Inclusion criteria: English language papers recounting empirical studies about: i) mental health nurses' routine physical healthcare-related knowledge, skills, experience, attitudes, or training needs; and ii) the effectiveness of interventions to improve any outcome related to mental health nurses' delivery of routine physical health care for mental health patients. Effect sizes from intervention studies were extracted or calculated where there was sufficient information. An integrative, narrative synthesis of study findings was conducted. Results Fifty-one papers covering studies from 41 unique samples including 7549 mental health nurses in 14 countries met inclusion criteria. Forty-two (82.4%) papers were published since 2010. Eleven were intervention studies; 40 were cross-sectional. Observational and qualitative studies were generally of good quality and establish a baseline picture of the issue. Intervention studies were prone to bias due to lack of randomisation and control groups but produced some large effect sizes for targeted education innovations. Comparisons of international data from studies using the Physical Health Attitudes Scale for Mental Health Nursing revealed differences across the world which may have implications for different models of student nurse preparation. Conclusions Mental health nurses' ability and increasing enthusiasm for routine physical healthcare has been highlighted in recent years. Contemporary literature provides a base for future research which must now concentrate on determining the effectiveness of nurse preparation for providing physical health care for people with mental disorder, determining the appropriate content for such preparation, and evaluating the effectiveness both in terms of nurse and patient- related outcomes. At the same time, developments are needed which are congruent with the needs and wants of patients.